Dampak Kerja Sama Perdagangan Indonesia dengan Negara Gulf Cooperation Council (GCC) - Paryadi, Deky (Badan kebijakan Fiskal, 2018)
The cooperation agreement with Saudi Arabia was proposed by Indonesia during the visit of King Salman bin Abdulaziz Al-Saud, King of Saudi Arabia to Indonesia, however given the membership of Saudi Arabia in the Gulf Cooperation Council (GCC), the trade cooperation can not be done bilaterally, so that the trade cooperation agreement will be conducted with the GCC. Therefore, it is necessary to see the impact that will occur if the trade cooperation with elimination of tariffs using Partial Equilibrium. Based on the simulation of Partial Equilibrium, Indonesia will get an import increase of GCC of USD 585.1 million, a welfare increase of USD 12.71 million, and will potentially lose state revenues of USD 173.67 million.